Metastatic sarcomatoid renal cell carcinoma manifesting as a subcutaneous soft tissue mass. (24th July 2017) - Logunova, Valentina; Sokumbi, Olayemi; Iczkowski, Kenneth A.
Abstract : Metastases from visceral malignancies to subcutaneous soft tissues are relatively rare and their diagnosis requires a high level of suspicion. It is even more challenging if a metastatic lesion shows non‐specific high‐grade spindle cell morphology overlapping with various primary cutaneous and soft tissue tumors. We describe a unique case of subcutaneous metastasis of sarcomatoid renal cell carcinoma which was the first manifestation of the occult malignancy. The patient had a history of lipomas and dysplastic nevi and presented with an upper back mass. The mass, located superficially within the subcutis, was composed of atypical spindle cells arranged in a storiform pattern. By immunohistochemistry, the tumor cells were strongly diffusely positive for cytokeratin AE1/AE3 and vimentin and negative for Melan‐A, S‐100 protein, SOX10, melanoma cocktail, epithelial membrane antigen (EMA), p63, CK7, CK18, CK20, smooth muscle actin (SMA), desmin, CD34, TTF‐1, CD21, CD99 and bcl‐2. Scattered tumor cells were positive for MDM2 immunostain, but MDM2 amplification was not detected using fluorescent in situ hybridization (FISH). Co‐expression of cytokeratin and vimentin by the tumor raised the possibility of metastatic renal cell carcinoma and positivity of the tumor for PAX8 supported this hypothesis. A large renal mass was detected radiologically and the subsequent nephrectomy specimen showed high‐grade clear cell renal cell carcinoma with sarcomatoid features.